Legal Technology and the Future of Women in Law - Munisami, Kayal (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2019)
Much has been written about how automation will change the legal profession as a whole, less so about how automation might affect women in legal practice. This paper briefly maps the likely changes that legal tech (legal technology) will bring to the provision of legal services, and explores how these changes might affect the barriers to advancement that women face in the profession. It determines that, while the use of legal tech may improve women’s work/life balance and overall job satisfaction by bringing about more flexible working hours, positive changes to the billing hours’ system, and fairer hiring and promotion mechanisms, an unfettered inclusion of legal tech might lead to increased working hours for less wages, increased competition for case files among associates, and the perpetuation of existing gender biases when using algorithms in the hiring and promotion process. Finally, the paper makes several recommendations on how law societies, bar associations and other relevant regulatory bodies could ensure that legal tech promotes rather than hinders Equality & Diversity in the legal profession. It proposes that: (1) detailed data on men and women lawyers should be collected to better inform equality and diversity policies; (2) law firms should be required to report on their progress in pursuing equality and diversity; (3) management techniques to promote work/life balance and more flexible pricing systems should be encouraged; (4) female entrepreneurship in legal tech should be promoted; and, (5) technological due process procedures should be required when using algorithms in law firm management to ensure fairness, accuracy and accountability.